Congenital duodenal web: successful management with endoscopic dilatation - Poddar, Ujjal; Jain, Vikas; Yachha, Surender Kumar; Srivastava, Anshu (Endoscopy International Open, 2016)
Background and study aims: Congenital duodenal web (CDW) is an uncommon cause of duodenal obstruction and endoscopic balloon dilatation has been reported in just eight pediatric cases to date. Here we are reporting three cases of CDW managed successfully with balloon dilatation.Cases and methods: In 2014 we diagnosed three cases of CDW on the basis of typical radiological and endoscopic findings. Endoscopic balloon dilatation was done under conscious sedation with a through-the-scope controlled radial expansion (CRE) balloon.Results: All three children presented late (median age 8 [range 2 – 9] years) with bilious vomiting, upper abdominal distension, and failure to thrive. One of them had associated Down syndrome and another had horseshoe kidney. In all cases, CDW was observed in the second part of the duodenum beyond the ampulla, causing partial duodenal obstruction. After repeated endoscopic dilatation (2 – 4 sessions), all three patients became asymptomatic. None of the patients experienced complications after balloon dilatation.Conclusions: Duodenal diaphragm should be suspected in patients with abdominal distension with bilious vomiting, even in relatively older children. Endoscopic balloon dilatation is a simple and effective method of treating this condition.